2015
DOI: 10.1016/j.cyto.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional cytokines: How catecholamines and adipokines influence macrophages in immunity, metabolism and the central nervous system

Abstract: Catecholamines and adipokines function as hormones; catecholamines as neurotransmitters in the sympathetic nervous system, and adipokines as mediators of metabolic processes. It has become increasingly clear, however, that both also function as immunomodulators of innate and adaptive immune cells, including macrophages. Macrophages can respond to, as well as produce their own catecholamines. Dopamine, noradrenaline, and adrenaline are the most abundant catecholamines in the body, and can induce both pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 90 publications
(100 reference statements)
2
78
0
1
Order By: Relevance
“…Host protection against STHs is dependent on the balance between effector immune responses that promote worm expulsion and immunoregulatory pathways that control excessive infection-induced inflammation (2). Resistin-like molecules (RELMs) are secreted proteins with putative effector and immunoregulatory functions against helminth infections (3,4). In humans, significant increases in resistin expression occur in both filarial nematode and gastrointestinal nematode infections (5,6).…”
mentioning
confidence: 99%
“…Host protection against STHs is dependent on the balance between effector immune responses that promote worm expulsion and immunoregulatory pathways that control excessive infection-induced inflammation (2). Resistin-like molecules (RELMs) are secreted proteins with putative effector and immunoregulatory functions against helminth infections (3,4). In humans, significant increases in resistin expression occur in both filarial nematode and gastrointestinal nematode infections (5,6).…”
mentioning
confidence: 99%
“…For instance, NE and E act as biomarkers in the study of diabetes, heart disease and anxiety. The deficiency of DA neurotransmission has been proved to be associated with Parkinson diseases and Chizophrenia [5,6]. For these reasons, the measurement of MNTs in biological samples is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…This involves direct effects on antigen-presenting immune cells or indirect effects via regulation of blood or lymphatic flow, regulation of distribution and production of lymphocytes, or modulation of proinflammatory peptide release. 10 Inflammatory cell recruitment and redistribution are also regulated by the sympathetic nervous system.…”
Section: Article See P 547mentioning
confidence: 99%
“…Major sympathetic neurotransmitters include norepinephrine, ATP, neuropeptide Y, and nitric oxide. 10 Although all these neorotransmitters directly influence immune cells, the best characterized is norepinephrine. This seems to hold true in Ang II-induced hypertension, where it was shown that dendritic cells express adrenergic receptors and that β2 receptor expression is increased.…”
mentioning
confidence: 99%